Kinetics of Oxalic Acid Catalyzed and Ultrasound-Assisted Hydrolysis of 3-Glycidoxypropyltrimethoxysilane and Structural Characteristics of the Resulting Aged Sonogels - Paccola, Carlos E. T. [UNESP]; Awano, Carlos M. [UNESP]; De Vicente, Fabio S. [UNESP]; Donatti, Dario A. [UNESP]; Yoshida, Makoto [UNESP]; Vollet, Dimas R. [UNESP] (American Chemical Society (ACS), 2015)
A kinetic study of the oxalic acid catalyzed and ultrasound-assisted hydrolysis of 3-glycidoxypropyltrimethoxysilane (GPTMS) was carried out using an ultrasound-adapted calorimetric method. During a relatively short time period (tp), the hydrolysis follows a heterogeneous pathway because of the initial immiscibility gap between GPTMS and water. Methanol produced in the early hydrolysis enhances the dissolution between GPTMS and water so that the hydrolysis crosses to a homogeneous pathway. A rate equation with a rate constant (k) of the order 3/4 with respect to GPTMS and first order with respect to water seems to describe well the experimental data in the homogeneous step of the reaction. k increased with increasing oxalic acid concentration up to a plateau value (∼3.2 × 10-3 M-3/4 s-1) at an oxalic acid concentration of about 0.083 M in the range studied (from 0.014 to 0.14 M). The rate constants k and 1/tp (proportional to k in the heterogeneous step) were found to follow approximately an Arrhenius equation with the hydrolysis temperature in the studied range (from 5 to 50 °C). The average activation energy for GPTMS sono-hydrolysis was found to be ΔE = (21.5 ± 1.9) kJ/mol. The structure of aged sonogels exhibited characteristics of a two-phase system (pore and hybrid solid phase) separated by a surface-fractal interface. The hybrid solid phase of the sonogels was constituted by polymeric linear chains, density fluctuation heterogeneities, and several intermolecular-interfering cagelike structures. The phase separation increased with increasing the hydrolysis temperature, apparently at the expense of the polymeric linear chains and the density fluctuation heterogeneities, and led to intensification of the intermolecular-interfering cagelike structures within the hybrid solid phase.